2013
DOI: 10.1111/are.12159
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects of a marine fish farm of gilthead seabream (Sparus aurata) in the NW Mediterranean Sea on water column and sediment

Abstract: WileyMorata Higón, T.; Falco Giaccaglia, SL.; Gadea, I.; Sospedra Ciscar, J.; Rodilla Alamá, M. (2013). Environmental effects of a marine fish farm of gilthead seabream (Sparus aurata) This study examined the effects of organic enrichment on water column, sediments and macrofauna caused by a fish farm in the Mediterranean Sea. Samples were collected on four sampling campaigns over a one-year cycle. Significant differences were found in the water column in dissolved oxygen, dissolved inorganic nitrogen, phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
3
18
0
2
Order By: Relevance
“…This can lead to an alteration of the distribution, type, and physiological activity of the benthic communities. Morata et al (2015), for instance, found a notable decrease in specific richness and a 9-fold increase in abundance under a NW Mediterranean seabream farm, similar to the one considered here, as compared to a control station.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This can lead to an alteration of the distribution, type, and physiological activity of the benthic communities. Morata et al (2015), for instance, found a notable decrease in specific richness and a 9-fold increase in abundance under a NW Mediterranean seabream farm, similar to the one considered here, as compared to a control station.…”
Section: Discussionsupporting
confidence: 81%
“…The highest concentrations are found relatively close to the individual fish pens, within a 100-m radius, but this distance depends strongly on the physical characteristics of the waste particles and on the variability of the prevailing water currents. The abundance of C at the seabed in this area modifies the redox potential (turning it more negative, Morata et al 2015) and increases the metabolism of the sediment, enhancing also oxygen consumption. This can lead to an alteration of the distribution, type, and physiological activity of the benthic communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in macrofauna, found in the farming area and the control station before cessation, were largely as a consequence of organic enrichment occurring in sediments under the cages (Morata et al ). C. capitata was found under the cages before the cessation in densities of 31,151 ind/m 2 , and it is thought to be an indicator par excellence of anoxic conditions (Rosenberg ) and is classified as an opportunistic species (Pinedo et al ).…”
Section: Discussionmentioning
confidence: 99%